Code-switching functions in postcolonial classrooms. Issue 3 (27th May 2018) - Chen, Yan; Rubinstein-Avila, Eliane
ABSTRACT: This paper focuses on code-switching (CS) in postcolonial (P-C) classrooms (e.g. Africa, Asia and Asia-Pacific) where the use of English has increased not only as a subject matter, but also as the language of instruction across all subjects. CS, a common behaviour among bilinguals and polyglots, refers broadly to the alternation between two or more languages or language varieties in a single conversation, and has received much attention—in terms of both its grammatical dimensions and sociolinguistic function. Rather than focusing on the grammatical dimensions of CS, this paper examines the sociolinguistic functions. The paper highlights attitudinal conflicts between educational language policies and classroom practices in regard to CS. Supporters argue that CS facilitates language learning and creates a supportive classroom environment. Opponents argue that it is counterproductive, because it does not foster acquisition in the second (or additional) language. This paper examines this conflict and highlights how it plays out in P-C classroom contexts. The authors provide implication for both classroom practice and future research.